Absolutely Lucy / : Three complete books and genre-by-genre teachers guide inside! - Cooper, Ilene; Harvey, Amanda (New York : Random House, 2004)
Bobby is a shy boy until he gets a beagle puppy named Lucy, who helps him to make new friends.
"A Stepping Stone book."
3.2
3-6
3-6.
School Library Journal
Book Links (A.L.A.)
Keywords: Bashfulness -- Juvenile fiction; Beagle (Dog breed) -- Juvenile fiction; Dogs -- Juvenile fiction; Bashfulness -- Fiction; Beagle (Dog breed) -- Fiction; Dogs -- Fiction; Shyness -- Fiction; Beagles -- Fiction; Dogs -- Fiction